MATHEMATICAL CONSTRUCTION OF DEFINITE INTEGRAL CONCEPTS BY USING GEOGEBRA - Sur, Widiya Astuti Alam (Study Program of Mathematics Education University of Muhammadiyah Malang, 2020)
The need to visualize concepts and support the materials in Mathematics learning by forming the pictures or by using existing draw, becoming what is needed by the students in improving their mathematical development and understanding. GeoGebra can combine dynamic visualization of geometry and the results of mathematical calculations simultaneously. The author examines the definite integral concept material of course, to then be explored with GeoGebra so that it is easily understood by students. The author studies the procedures for using GeoGebra, studies and constructs the concept of definite integral concepts, into a simulation and visualization in the form of GeoGebra files, which are ready to be used in the learning of definite integral concepts.